O Comitê de bacia como instrumento de democratização dos recursos hídricos. Um estudo de caso: a atuação do comitê da Bacia do Acaraú – Ceará - Moreira, Daniel Sanford (2014)
This study deals with the experience of the Acaraú Basin Committee, the process democratization of the Water Resources Management in Acaraú region bathed by the Acaraú River, in the State of Ceará, Brazil. The deployment of Acaraú basin committee brought to the local community the opportunity to meet and discuss key aspects of the decentralization and democratization of the State Water Resources Policy Process, provided by laws that now govern the participatory management of water resources both at the state level as federal. Novel experience for most members of the committee makes room for new paradigms in defining the participatory management process to follow, since the decision making run of discussion and deliberation at meetings of the committee members on the basis of management tools. The empowerment and recognition of the Acaraú Basin Committee brings the perspective of consolidating space resolution of the State Policy for Water Resources in the region. The aim of this study was to evaluate the advances in water resources of the State of Ceará, through the Basin Committees policy as an instrument of democratization of water resources in the river basin Acaraú. The paper is organized into five chapters. The Introduction deals with the statement of the problem, the scope of work and discusses how the document is organized. The Chapter 2 presents a literature review and legal bases; the Chapter 3 presents the methodology used for the study in question, and describes the Committee of River Basin Acaraú; the Chapter 4 presents the results of research; finally, chapter 5 presents conclusions of this research and makes some suggestions of complementary studies.